Considerations of Potential Proposals to Change the Model of Financing Educational Tasks in Local Governments - Kowalska, Iwona (Olsztyn Economic Journal, 2018)
The adopted system of financing educational tasks by local governments (LSGs), which allocates resources by reference to a funding formula ‘per pupil’, is no longer in tune with the changing socio-economic context of the development of Poland. The aim of this article is to identify the considerations which should be taken into account in the construction of a new model of funding school educational tasks by local governments. The study involved a desk based literature review and a ratio analysis of the financial condition of LSGs (indebtedness). The conducted analyses imply that the following issues need to be addressed: guaranteed financial independence of the local government as the governing body for educational institutions; transition from the ‘per pupil’ to ‘per class’ formula in allocating public resources; and guaranteed adequacy of public fund transfers for changes resulting from educational system reforms. If the above-mentioned conditions addressing financial, legal, demographic and political contexts are taken into consideration, the changes to the model of financing educational tasks will have a systemic character.